Nickel Oxide (NiO) Thin Film Synthesis via Electrodeposition for Methylene Blue Photodegradation - Mokhamad Ali Rizqi Maulana; Aisyaturridha; Salmah Cholilah; Fitria Dwi Arista; Bagus Nur Listiyono (Chemistry and Materials, 2023)
Nickel oxide (NiO) is an ideal photocatalyst material for methylene blue photodegradation. NiO is known to have high photocatalytic activity, good stability, and non-toxic properties. However, conventional NiO thin film synthesis methods are inefficient because require high temperatures, complex equipment operations, and volatile precursor solutions. Therefore, in this study, NiO was synthesized by the electrodeposition method and then applied for methylene blue photodegradation. NiO thin film's morphological structure and elemental composition percentage were characterized by field emission scanning electron microscopy and energy-dispersive X-ray spectroscopy, respectively. Meanwhile, the crystal structure was characterized using an X-ray diffractometer. Several electrochemical and photodegradation tests were conducted to analyze the performance of the NiO photocatalyst. The results showed NiO was successfully synthesized using the electrodeposition method.  The morphology of NiO was a coral-like structure. A sharp diffraction peak with high intensity at 2  with 43.28° indicates a well-ordered crystalline of NiO. The maximum photocurrent density generated from the photoelectrochemical test was 0.1287 mA/cm2. The small charge transfer resistance value (1353.6 Ω) confirmed from the electrochemical impedance spectroscopy test indicates low charge transfer resistance. Percent photodegradation of methylene blue was obtained at 65% in 100 min, which indicated good photocatalytic activity.